Peningkatan Hasil Belajar Siswa Melalui Penerapan model pembelajaran Think Talk Write Berbantuan Media Pop Up Book dilengkapi Crossword Puzzle - Nopri Podu Loya; Anita Tamu Ina; Marleni Rosalia Ndapa Huda (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – The purpose of this study was to improve student learning outcomes using the Think Talk Write (TTW) learning model, supported by pop-up books and crossword puzzle worksheets.Methods – The research was conducted in three cycles in the eighth grade at SMP Negeri 4 Umbu Ratu Nggay. The material used in this study was Introduction to Cells. Therefore, each cycle was implemented three times. The stages in each cycle were planning, implementation, observation, and reflection. A post-test was administered at the end of each session to assess student learning outcomes.Findings – The student learning completion rate at the beginning of the pre-cycle was still very low, reaching only 11% (2 students), with 89% (16 students) considered incomplete. Following the first cycle, 44 students (8 students) achieved completeness, with the remaining 56% (10 students) still categorized as incomplete. After that, in the second cycle, the student learning completion rate reached 72% (13 students), with 28% (5 students) remaining incomplete. The average pre-cycle test score was 47.22, the average test score in the first cycle was 51.11, and the average score in the second cycle was 64.44. Research Implications – This study, categorized as Classroom Action Research (CAR), applies the Think Talk Write learning model, supported by pop-up books and crossword puzzles, which are highly effective in improving learning outcomes.